Čekoslovakijos diplomatinės tarnybos Lietuvoje (1921-1939 metais) klausimu - Bukelevičiūtė, Dalia (Lietuvos istorijos studijos, 2004)
The problem of diplomatic relations between Lithuania and Czechoslovakia is that Lithuanian historiography has not been investigated yet. There are very important L Švec works from the Czech historians. The base of this article is material from Lithuania and Czech Republic archives.  Recognition of de jure question and the entering into diplomatic relations with Lithuania and Czechoslovakia were discussed together. At the Paris Peace Conference, Czechoslovakia considered Lithuania as a part of the Russian question. Only in 1921 autumn Lithuania and Czechoslovakia exchanged non-official representatives. In 1921 12 29, Czechoslovakia recognized Lithuania de jure and excluded it from the Russian question. In 1922, Czechoslovakia's diplomatic representative in Kaunas, J. Galia, became a consul.  J. Galia (1921-1928), M. Niederle (1928-1933), and J. Skalicky (1933-1939) represented Czechoslovakia's interests in Lithuania. Only J. Skalicky was the ambassador extraordinary from 1936. The possibility to replace the consulate of Czechoslovakia with the embassy of Czechoslovakia in Kaunas was discussed in the ministry of foreign affairs of Czechoslovakia in 1927. The embassy was opened only formally: the ambassador extraordinary resided in Stockholm (till 1936), whereas a consul in Kaunas got the charge d'affaires title. In 1925, J. Galia provided an honour consulate in Klaipėda (the first consul was M. Reišys; from 1933 - J. Galia junior).  One of the most important questions raised by the Ministry of Foreign Affairs of Czechoslovakia for its diplomatic corps was the ability to make and develop the diplomatic contacts. Diplomats were also charged to care about the political questions and follow the different changes in the country. They informed the Ministry of Foreign Affairs of Czechoslovakia about the political and economic questions in their political reports.  J. Galia - the first Czechoslovakia representative - was a very active diplomat because of his personal characteristics. He succeeded in good relations with Lithuania's politics. Being in Kaunas, he personally worked on the question that Lithuania would officially be recognised de jure by Czechoslovakia as soon as possible. Also, J. Galia invited trades of Lithuania and Czechoslovakia to participate in exhibitions and encouraged them for close inter-cooperation. The import of Czechoslovakia to Lithuania increased significantly during his term of office in Kaunas.  M. Niederle's relations with Lithuania's politics were not very good. In 1928-1933 (the period he worked in Kaunas), the political cooperation was small. His role in solving political problems is not remarkable. Lithuania's trade began to orientate towards the England's market during the 4th decade; therefore, M. Niederle cared about strengthening of Czechoslovakia's interests in Lithuania's market.  J. Skalicky was the most active in the political cooperation between Lithuania and Czechoslovakia. Lithuania's politics were informed of German aggression to the Middle Europe by him. J. Skalicky had close contacts with the minister of Lithuania's Foreign Affairs - S. Lozoraitis. He also cared about the maintenance of Czechoslovakia's economic interests in Lithuania. During personal contacts with official persons of Lithuania, J. Skalicky always marked the importance of such relationships.